ORIGINS OF PSYCHOLOGICAL THOUGHT AND NATIONAL PSYCHOLOGICAL IMAGE IN UZBEKISTAN - Atadjanov Mamirjon Yusupovich (Bright Mind Publishing, 2025)
The strengthening of the national paradigm in different parts of the world as a result of information influence with the aim of introducing into the public consciousness values that are contrary to national identity gives rise to the need to revise the origins of psychological thought and the national psychological image. The article highlights religious and philosophical schools in the history of Islam and the teachings of great thinkers of the Muslim Renaissance period as the sources of psychological thought and the national psychological image in Uzbekistan.
Keywords: Manichaeism, mazdakism, ismailism, mu'tazilites, sufism, jadidism, the teachings of Farabi, Ibn Sina